TEJIENDO VÍNCULOS, HACIA LA CONSTRUCCIÓN DE REDES DE CONOCIMIENTO Y ACCESO A RECURSOS EN MICROEMPRESAS RURALES CASOS: LOS CASOS JUVELIN EN CHIHUAHUA Y MAXES EN SONORA - Ana María Arras Vota (European Scientific Journal, ESJ, 2013)
respond to the need for employment in the rural sector, some people have opted for the creation of small businesses related to the knowledge of the production process that they have, and that in many cases it has been to them transferred by their parents. These non-agricultural businesses contribute to economic development, using the opportunity of the natural resources they possess.One of the options that rural enterprises have is the incorporation to value chains that will allow them to acquire knowledge about the production processes, marketing, financing options and other resources that can support them at every stage of the business, from production to consumer. These ties are transformed into networks of relationships through which knowledge is created and transferred.Through two case studies, this paper describes the first phase in the construction of the network of each one of the companies under study and then the way in which each one was acquiring contacts and knowledge that enabled them to expand their network and achieve social capital and the possibility to move forward and develop.